2020
DOI: 10.3390/rs12142242
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics of Cloud Occurrence and Vertical Structure Observed by a Ground-Based Ka-Band Cloud Radar in South Korea

Abstract: The cloud measurements for two years from the vertical pointing Ka-band cloud radar at Boseong in Korea are used to analyze detailed cloud properties. The reflectivity of the cloud radar is calibrated with other vertical pointing radars compared with the two disdrometers. A simple threshold-based quality control method is applied to eliminate non-meteorological echoes (insects and noise) in conjunction with despeckling along the radial direction. Clouds are classified into five types: high (HC), middle (MC), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This regime shift induced the updraft (reached 1 m s −1 ) below this layer. However, Ye et al (2020) could not explain the linkage between this regime shift and updraft below. While it is beyond the scope of this study, this phenomenon will be an interesting topic for future research on cloud microphysics in this region.…”
Section: Vertical Structuresmentioning
confidence: 84%
See 2 more Smart Citations
“…This regime shift induced the updraft (reached 1 m s −1 ) below this layer. However, Ye et al (2020) could not explain the linkage between this regime shift and updraft below. While it is beyond the scope of this study, this phenomenon will be an interesting topic for future research on cloud microphysics in this region.…”
Section: Vertical Structuresmentioning
confidence: 84%
“…A similar feature also appeared in the long-term observations with cloud radar (see Figs. 16 and 17 of Ye et al, 2020). The shift in growth regime appeared at 8 km height (3-3.5 km above the bright band peak and corresponding to ∼ −17 • C).…”
Section: Vertical Structuresmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies have revealed the cloud vertical structure and statistical characteristics of cloud base height, top height and geometrical depth using CloudSat, CALIPSO, MODIS, AIRS, MISR, GLAS and TOGA/COARE [5][6][7]9,10,[12][13][14][15][16][17][18]. There have also been extensive studies using ground-based and in-situ measurements, such as lidar and radar [7,12,[14][15][16][19][20][21][22][23][24][25], radiosonde [10,15,21,25], ceilometer [11] and meteorological station observations [26,27]. These studies have used different means to study the distribution characteristics of clouds in different regions, each with its own advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue in Remote Sensing on "Winter weather research in complex terrain during ICE-POP 2018" included some of the ICE-POP 2018 results that can be used to envision the future of the field [2][3][4][5]. Additional contributions in the "Precipitation and Water Cycle" Special Issue can also help unravel the many dimensions of precipitation science, including ground observations (rain gauges, ground radars, disdrometers), satellite estimates (radars, radiometers) and models, including numerical weather prediction (NWP) models, regional climate models (RCMs), global climate/circulation models (GCMs), Earth system models (ESMs) and variable resolution models (VRMs) [6][7][8][9][10][11].…”
mentioning
confidence: 99%